Budesonide, fluticasone propionate, and azithromycin do not modulate the membrane vesicle release by THP-1 macrophages and respiratory pathogens during macrophage infection - Volgers, Charlotte (Inflammopharmacology, 2017)
Patients with more severe chronic obstructive pulmonary disease frequently experience exacerbations and it is estimated that up to 50% of these exacerbations are associated with bacterial infections. The mainstay treatment for these infection-related exacerbations constitutes the administration of glucocorticoids, alone or in combination with antibiotics. A recent line of evidence demonstrates that many hormones including the steroid beclomethasone can also directly affect bacterial growth, virulence, and antibiotic resistance. The effect of these regimens on the release of potentially virulent and toxic membrane vesicles (MVs) is at present unclear. In this study, we determined the effect of several pharmacological agents on MVs release by and bacterial growth of common respiratory pathogens. We found that neither the release of MVs nor the bacterial growth was affected by the glucocorticoids budesonide and fluticasone. The macrolide antibiotic azithromycin only inhibited the growth of Moraxella catarrhalis but no effects were observed on bacterial MV release at a concentration that is achieved locally in the epithelial lining on administration. The macrophage pro-inflammatory response to MVs was significantly reduced after treatment with budesonide and fluticasone but not by azithromycin treatment. Our findings suggest that these glucocorticoids may have a positive effect on infection-related inflammation although the bacterial growth and MV release remained unaffected.